Evaluasi Reformasi Kepolisian dalam Menangani Anak Berhadapan dengan Hukum - Rizanizarli Rizanirarli (Universitas Syiah Kuala, 2011)
ABSTRACT: Professional and accountable police in treating people by respecting the democratic norm and human rights is the goal of the police. However, since the change started, there are complaining because it is done slowly. Treating the juvenile offenders is one of the forms; the police have been protected by several special rules for the best need of the offenders. The police as investigatiors is the first institution in the process of formal criminal justice procedure that have an important rle causing the children arresed and imprisoned. It may happen because of lack of knowledge, and too strict in implementing it, lacking the understanding about the children rights and human rights especially diverted and restorative justice concepts. The reforms that are being done is still weak because of the police and social structure that are still inherit the militeristic character. It can be seen from the abuse done toward them and there is no justice for the violation done by the police. Nevertheless, the problem is also should be solved by the people because this is also the problem for the people; hence no one should be blamed for it. The Evaluation of Police Reform in Treating Juvenile Offenders